AB1231 Pericardial effusion is more frequent in patients with familial mediterranean fever during attack period: An echocardiography study from central part of turkey. (23rd January 2014) - Senel, S.; Gul, I.; Ataseven, H.; Uslu, A.U.; Sahin, S.
Abstract : Background: Familial Mediterranean fever (FMF) is an autoinflammatory disease of obscure pathogenesis with autosomal recessive heredity, which mainly affects people of Mediterranean origin, especially Jewish, Turkish, Armenian and Arabic population. The disease is characterized by recurrent episodes of febrile serositis and manifested primarily as abdominal, chest, and joint pain. Objectives: Pericardial involvement in FMF patients has been determined by several researches at different rates, including with or without echocardiographic examination. However, there is no enough data about it yet. The primary aim of this study was to define the frequency of pericardial effusion (PE) in patients with FMF during attack period with echocardiography. Methods: The study population was selected from patients admitted to the rheumatology clinic of our center with FMF attack. The FMF diagnosis was made according to Tel–Hashomer criteria. The attack period was ensured with laboratory findings and clinical decision of a rheumatologist. M mode and Doppler echocardiographic examinations were performed. Pericardial effusion was graded as: small, moderate and large. Attacks were grouped as presence of PE; Group I (without PE) and Group II (with PE). Results: Forty three attacks of 37 patients were investigated. There were 11 male, 26 female; mean age was 33±12 years and the disease (FMF) duration was 13±9 years. The frequency of PE was determined as 30% (13/47). All PE was at small grade and have clear view on echocardiography. Echocardiography has not revealed segmental wall motion abnormalities in any patient. After dividing patients as presence of PE, 30 patients were in group I, 13 patients were in group II. When we compared, basal characteristics, echocardiographical and laboratory findings the presence of PE was not related to gender, usage of colchicines or response to colchicines. Mean age of group II was significantly higher; 31±12 vs. 39±7.5; p=0.012. The disease duration and age of diagnosis were higher in group II, the differences was borderline to statistical significance; p=0.058, p=0.055, respectively. All patients had normal ECG. Echocardiography has not revealed segmental wall motion abnormalities in any patient and all had normal left ventricular ejection fraction. Conclusions: The main finding of the study is that the frequency of PE is 30% in our FMF cohort during attack period. Older patients and patients with longer disease duration are seem to more prone to develop pericardial involvement. Our finding supported the previous studies reported by Terekeci (1) and Dabestani (2) et al. that the incidence of PE were 23, 3% and 27%, respectively. PE showed that minimal PE is more frequent than previous studies and can be easily diagnosed with echocardiography in patients with FMF during attack period. References: Terekeci HM, Ulusoy ER, Kucukarslan NM, Nalbant S, Oktenli C. Familial Mediterranean fever attacks do not alter functional and morphologic tissue Doppler echocardiographic parameters. Rheumatol Int. 2008 Oct;28(12):1239-43. Epub 2008 Jul 23. Dabestani A, Noble LM, Child JS, Krivokapich J, Schwabe AD. Pericardial disease in familial Mediterranean fever: an echocardiographic study. Chest. 1982 May;81(5):592-5. Disclosure of Interest: None Declared